Drugs from poisonous plants: Ethnopharmacological relevance to modern perspectives - Bhagya Lakhmi Rajbongshi; Ashis K. Mukherjee (Toxicon: X)
The world of plant diversity is endlessly fascinating and essential for life on Earth. Since the inception of early civilization, humans have utilized plants for several purposes, particularly for their medicinal value. While some plants are known for their toxicity, they also contain beneficial phytochemicals that are important for both plants and humans, indicating their dual nature. This study aims to explore and synthesize the existing knowledge on various poisonous plant species found worldwide. It primarily focuses on the therapeutic potential of specific types of phytochemicals responsible for treating multiple diseases. This review includes a list of 70 poisonous plants with medicinal properties for treating various ailments, as well as some of their traditional uses. A few of these plants are emphasized, which have been tremendously explored and studied, hold significant potential to contribute to modern drug discovery. Furthermore, it addresses the possible prospects and challenges of using poisonous plants and their phytochemicals as therapeutic agents. Although the therapeutic potential of poisonous plants is substantial, many toxins remain unexplored. This review accentuates the need for rigorous scientific investigations, prior to clinical trials to validate their traditional uses, which would reveal the pharmacological interventions that will eventually advance human health and well-being.